2017
DOI: 10.1002/asna.201713339
|View full text |Cite
|
Sign up to set email alerts
|

Tidal disruption of stars by super‐massive black holes—XMM‐Newton highlights and the next decade

Abstract: This article provides a summary of XMM-Newton highlights on stellar tidal disruption events. First found with ROSAT, ongoing and upcoming sky surveys will detect these events in the thousands. In X-rays, tidal disruption events (TDEs) provide us with powerful new probes of accretion physics under extreme conditions and on short timescales and of relativistic effects near the super-massive black holes (SMBHs), of the formation and evolution of disk winds near or above the Eddington limit, and of the processes o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Even, during the declining period of the 2018 outburst, Oknyansky et al (2020) observed 3 additional bursts in ∼ 1 year. The theoretical rate of TDEs is too low ∼ 10 −4 − 10 −5 galaxy −1 year −1 (See, Kawamuro et al 2016, Komossa 2015, and references therein) to produce such repetitive events. Also, the X-ray spectra of NGC 1566 are harder than a typical X-ray spectrum of TDEs (Komossa 2015(Komossa , 2017.…”
Section: Spectral Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even, during the declining period of the 2018 outburst, Oknyansky et al (2020) observed 3 additional bursts in ∼ 1 year. The theoretical rate of TDEs is too low ∼ 10 −4 − 10 −5 galaxy −1 year −1 (See, Kawamuro et al 2016, Komossa 2015, and references therein) to produce such repetitive events. Also, the X-ray spectra of NGC 1566 are harder than a typical X-ray spectrum of TDEs (Komossa 2015(Komossa , 2017.…”
Section: Spectral Transitionmentioning
confidence: 99%
“…The theoretical rate of TDEs is too low ∼ 10 −4 − 10 −5 galaxy −1 year −1 (See, Kawamuro et al 2016, Komossa 2015, and references therein) to produce such repetitive events. Also, the X-ray spectra of NGC 1566 are harder than a typical X-ray spectrum of TDEs (Komossa 2015(Komossa , 2017. Thus, the TDEs are unlikely to be responsible for the burst activities in NGC 1566.…”
Section: Spectral Transitionmentioning
confidence: 99%
“…galaxies (Komossa 2017), or verifying signatures of General Relativity (delay in accretion disk formation or quasi-periodic modulations at Xrays; Stone et al 2018).…”
Section: Tidal Disruption Eventsmentioning
confidence: 99%
“…以上 [26,27] , 而J1231+1106自爆发后10年内仍有较强的X 射线辐射, 这可能与吸积气体的轨道圆化和超爱丁顿 吸积过程有关 [28,29] [23] Figure 5 (Color online) (a) Sustained, short, intense soft X-ray outbursts from RX J1302+2747; (b) energy spectra of the source during its quiescent and flare states (data from Chandra and XMM-Newton) [23].…”
Section: Tde X射线辐射在其爆发后1年以内减弱约一个量级mentioning
confidence: 99%